Bananas persisting: Food and fibre crops in an Ugandan village in 1937 and 1994 - Davies, G.; International Plant Genetic Resources Institute (1995)
This study was conducted in July 1994 in Bukeeka-village, a bimodal highland banana producing area of Luwero District, Central Uganda. Its principal objective was to review continuity and change in agricultural production at farmer level. An inventory of names of crop-plants and of socio-economic activities in Bukeeka land had been recorded by the Senior Botanist of the Agriculture Department Government of Uganda, during a village survey in 1937. The 1994 study draws on the 1937 village monograph to identify changes in production and, when possible, to register farmer evaluation of named varieties of bananas and other economic plants. In 1994, household level interviews were conducted in a sample of six banana-farming households. These interviews aim at identifying of factors influencing farmer decisions to retain or vary production of food and fibre crops. They also attempt to describe social and economic priorities of farmers and to indicate constraints to production encountered by farm-households.